“Kang Pisang”: Personal Branding of the Jokowi’s Youngest Son in the Microblogging Media - Marshelia Gloria Narida (Universitas Mataram, 2019)
Awareness in using the technology for building a self brand through personal branding can appear in anyone, whether from the public figures, nor from the society in general. The youngest son of Presiden Joko Widodo (Jokowi), Kae Sang Pangareb (Kae Sang) is known as an person who has a high level of awareness on her social media. This study examines trends in shaping the content of microblogging as a personal branding of Kae Sang. Studies conducted on the accounts twitter Kae Sang (@kaesangp) by looking at twitter account contents and personal branding process through microblogging. According to personal brand buildings theory by Peter Montoya, this research take 8 personal brand building category, specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and good will. It can be conveyed that the personal branding of Kae Sang on twitter complies with the criteria of the forming of personal brandingKeyword : Personal Branding; Microblogging; Twitter